Cells - Duke, Shirley Smith (2014)
Explains the discovery of cells, what cells are, the kinds of cells, cell reproduction, and more.
Discovering cells -- What's in a cell? -- Kinds of cells -- Control center -- Making more cells -- How scientists study cells -- Stop and think -- Glossary.
School Library Journal, April 2014
Includes bibliographical references (p. 47) and index.
5.1
3-6
Keywords: Cells -- Juvenile literature; Cytology -- Juvenile literature; Cells; Cells